Efek Jus Terung Pirus (Cyphomandra betacea Sendtn.) Terhadap Jumlah Sel Darah Merah (Eritrosit) Dan Nilai Hematokrit Pada Mencit Putih Jantan - Yufri Aldi; Yanelita Vipri; Zet Rizal (Jurnal Farmasi Higea, 2013)
Evaluation about the effect of pirus juice (Cyphomandra betacea Sendtn.) on hematology parameters (red blood cells, reticulocytes, hemoglobin and hematocrit) for male white mice has been done. The juice was administrated orally one times a day during 20 days.  The 1th day until the 20th day the animal induction with Chloramphenicol 130 mg / kg orally, followed by the provision of pirus juice with various doses of 0.26 mL and 0.52 mL. The effect was observed on day 5, 10, 15, 20, 25 and 30. The result showed that administration of pirus juice can increase the number of red blood cells, reticulocytes, hemoglobin and hematocrit  male white mice at each dose is highly significant (p <0.05). Dose of 0.52 mL of the nicest effects compared with other doses (p <0.05).